Pengembangan Layanan Web Service Data Akademik Pada Universitas Atma Jaya Makassar - Raymond Rianto (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2017)
Governance academic process is one form of infrastructure utilization of information and communication technology in higher education. University of Atma Jaya Makassar (UAJM) is one of the campus that have using the governance academic process in conducting its function as a higher education. Governance academic process consists of multiple systems where each system has a database structure and different system models. This has become one of the major constraints in generating relevant data and real time. This research aims to integrate existing systems in the governance academic process at UAJM. The approach can be used to integrate these systems, the application of SOA (Service-Oriented Architecture). In this research, the authors use the web service in applying SOA to the integration of governance academic process in UAJM. Results from this research is a system that is integrated with web service application to meet the criteria SOA-based systems. The impact of an integrated system will produce accurate data and real time for each user.